2017
DOI: 10.1002/j.1681-4835.2017.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of Employees and Customers’ Responses in Determining the Technological Innovativeness of Banks

Abstract: The banking sector globally is saddled with intensified competition. Coupled with global economic situation of little tolerance for inappropriate resources usage, financial institutions have to pursue different strategies to meet the challenges and opportunities of providing quality services to existing customers, attract new customers, improve the turnover of employee, and increase long-term firm performance. Innovation and technology are considered fundamental elements of strategic management. Implementing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…e adoption of innovation in the Banking Sector has facilitated transactions and business worldwide. Internet banking structures, such as electronic checks payment system, Automatic Teller Machines (ATMs), credit visa, debit and master cards, mobile banking applications, etc., have transformed the world where clients may be able to purchase and sell goods and services, and also can make money transactions through the use of Internet [7,14,17,18]. Chai et al [5] have confirmed that the introduction of Internet banking has increased efficiency, effectiveness, and productivity levels in the banking industry.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
See 1 more Smart Citation
“…e adoption of innovation in the Banking Sector has facilitated transactions and business worldwide. Internet banking structures, such as electronic checks payment system, Automatic Teller Machines (ATMs), credit visa, debit and master cards, mobile banking applications, etc., have transformed the world where clients may be able to purchase and sell goods and services, and also can make money transactions through the use of Internet [7,14,17,18]. Chai et al [5] have confirmed that the introduction of Internet banking has increased efficiency, effectiveness, and productivity levels in the banking industry.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
“…ey further suggested that, it is required to improve conditions of access in providing satisfactory high-speed connectivity and infrastructure of Internet services; to reduce costs related to Internet connection by supporting healthy competition among service providers; and to impart digital literacy to individuals who may highlight the benefits and advantages provided by the usage of Internet. Technology answers can help a financial institution to innovate on methods such as digital dispersal of banking correspondence, direct banking, tolerating electronic documentation from clients [38], enhancing employee performance, and lowering inefficiencies [18]. Siddik et al [4] researched the impact of innovative technology on the profitability of Bangladeshi banks.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
“…In Thailand, attempts have been done on the national level to increase technological innovation in the durian business. Technological innovations are a result of the competition in processes (Obeng & Mkhize, 2017).…”
Section: Level Of Competition Technological Innovativeness and Durimentioning
confidence: 99%
“…Regarding the aspect of skills, [25] observed that IT implementation leads to enhanced skill compatibility among banking aspects, an outcome that was documented to be a pointer or predictor of improved employee productivity. As avowed by [26] say an additional attribute that leads to insights regarding the relationship between IT implementation and HR management (as well as the performance of banking institutions) involves competence. Particularly, the study indicated that through IT implementation, bank employees exhibit competence because they believe that they possess the required skills and capabilities to implement and learn e-banking; with the confidence also making them be part of and participate in IT implementation; especially after undergoing adequate training.…”
Section: Review Of Literaturementioning
confidence: 99%